Metamorphic rocks from the north-eastern part of the Ereendavaa terrane (Eastern Mongolia) :: an origin of the Permian back-arc basin rather than the Proterozoic basement - Narantsetseg, Tserendash; Chao, Yuan; Tao, Wang; Zhongyuan, Ren; Pengfei, Li; Le, Zhang; Lei, Guo; Ying, Tong; Orolmaa, Demberel; Battushig, Altanbaatar; Baatarchuluun, Orosoo; Idermunkh, Tuya; et al. (Mongolian Geoscientist, 2021)
In this paper, we have conducted geochronological and geochemical studies on the metamorphic rocks of the Khaychingol and Ereendavaa Formations in the Mogoitiin Gol, Khaychin Gol and Emgentiin Bulag areas from the Ereendavaa terrane and these rocks have been considered to be Precambrian in age. However, new LA–ICP–MS zircon U–Pb dating results indicate that the protolith of the studied metamorphic rocks was formed in two stages: 1) during ~ 296 - 285 Ma, the protolith of mafic, felsic and black schists formed; 2) during ~276 - 271 Ma, the protolith of gneiss and psammitic schists began to deposit. The Early Permian bimodal association composed of low-K basalt and comagmatic high-Na, low-K dacite with high-K calc-alkaline rhyolite, represent protolith of the mafic and felsic schists which were formed in back-arc basin environment. The Middle Permian gneiss, and psammitic schists with sedimentary protolith have geochemical signatures of island arc rocks, such as enrichment of LILE relative to HFSE, and markedly negative Nb, Ta and Ti anomalies, suggesting that they were formed in a continental arc environment. Considering a close spatial relationship of the Ereendavaa terrane with the Mongol-Okhotsk Belt in the north-west, we propose that accompanied with the emplacement of arc magmatic rocks, the arc rifting occurred and formed the Early Permian bimodal volcanic rocks. In the Late Permian, after the formation of the back-arc basin, deposition of the immature deposits as wacke, arkose and litharenite dominated sediments in a continental arc environment started.